The study of maternal and perinatal outcome in prolonged pregnancy - Singh, Shivani; Gupta, Hem Prabha; Verma, Urvashi; Yadav, Gunjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prolonged pregnancy or post-dated pregnancy is that pregnancy which has exceeded duration considered to be upper limit of normal pregnancy that is above 40 completed weeks or 280 days from the first day of last menstrual period. The objective was to evaluate the maternal and perinatal outcome of post-dated pregnancy. Methods: A prospective case control study was conducted on antenatal women for 18 months period from May 2014- October 2015 admitted to the Obstetrics and Gynecology Department, Era’s Lucknow Medical College and Hospital, Lucknow, Uttar Pradesh, India. The study group was comprised of antenatal women having pregnancy beyond 40 weeks, and the control group was represented with antenatal women between 37-40 weeks admitted for delivery during this period. Results: The prevalence of post-dated pregnancy was found to be 17.6% and of post-term was 5.69%. Among post-dated subjects LSCS rate was 56.50% and in term (37-40 weeks) patient it was 34.18%. The NICU admission for birth asphyxia was 6.09% among term (37-40 weeks) patients and 17.6% in post-dated pregnancies. Conclusions: Any pregnancy that crosses expected date of delivery, Foetal well-being must be assessed and induction of labour should be considered to decrease the risk of perinatal morbidity and mortality.